Periodic Unsteady Flow Aerodynamics and Heat Transfer: Studies on a Curved Surface, Combined Part I and II - M. T. Schobeiri; L. Wright; P. Chakka (International Journal of Rotating Machinery)
Aerodynamic and heat transfer investigations were done on a constant curvature curved plate in a subsonic wind tunnel facility for various wake passing frequencies and zero pressure gradient conditions. Steady and unsteady boundary layer transition measurements were taken on the concave surface of the curved plate at different wake passing frequencies where a rotating squirrel-cage generated the unsteady wake flow. The data were analyzed using timeaveraged and ensemble-averaged techniques to provide insight into the growth of the boundary layer and transition. Ensemble-averaged turbulence intensity contours in the temporal spatial domain showed that transition was induced for increasing wake passing frequency and structure. The local heat transfer coefficient distribution for the concave and convex surface was determined at those wake passing frequencies using a liquid crystal heat transfer measurement technique. Detailed aerodynamic and heat transfer investigations showed that higher wake passing frequency caused transition to occur earlier on the concave surface. Local Stanton numbers were also calculated on the concave surface and compared with Stanton numbers predicted using a differential boundary layer and heat transfer calculation method. On the convex side, no effect of wake passing frequency on heat transfer was observed due to a separation bubble that induced transition.